The implementation of special attributes of CEO compensation contracts around M&A transactions - Bodolica, Virgínia; Spraggon, Martin (Strategic Management Journal, 2009)
Abstract This study investigates how the implementation of special attributes of CEO compensation contracts is determined by both the acquisition and the acquirer features for a set of M&A deals undertaken by Canadian acquiring firms. Our findings reveal that when agency problems are higher, manifested by larger control premiums and poor firm performance, boards of directors tend to implement stronger mechanisms of incentive alignment around M&A transactions. Relying on multiple interdisciplinary logics that are activated to explain directors' ability to effectively perform their monitoring function, we show that boards are reactive rather than proactive in dealing with agency problems. Data are further interpreted in light of the unique aspects of the Canadian institutional context. Based on asymmetric risk properties of two different groups of executive compensation modes examined in this study, testing the substitution effects between alternative governance mechanisms is proposed as an interesting avenue for future research. Copyright © 2009 John Wiley & Sons, Ltd.